Durability Comparison of SKD61 and FDAC Steel Mold Inserts in High-Pressure Die-Casting Process - Nguyen Le Dang, Hai; Nguyen, Van-Thuc; Hoang, Van Huong; Vo, Xuan Tien; Nguyen, Van Thanh Tien (Machines (Basel), 2025)
The high-pressure die-casting (HPDC) process involves injecting molten light metal into a steel mold under high pressure, resulting in parts with excellent surface quality and precise dimensions. However, this process subjects the mold to thermal fatigue and mechanical stress, which can lead to damage over time. This study investigated the wear characteristics of two types of inserts made from different steel materials, SKD61 steel and FDAC steel, under HPDC conditions. A thorough approach that combined computer simulations, experiments, and 3D scanning was employed to analyze wear patterns and dimensional changes after up to 300 casting cycles. The results indicate that the SKD61 steel outperformed the FDAC steel in terms of wear resistance and dimensional stability. The maximum deposition values of the SKD61 mold were only 0.009 mm, which was only 25% compared to the FDAC mold, indicating a significantly higher wear resistance. These findings are crucial for selecting and enhancing insert materials in HPDC, ultimately leading to higher-quality and more efficient casting.